An evaluation of the law and practice in Tanzania in realising the rights of vulnerable children in street situations - Kisinza, Mercy-Grace Lameck (Department of Public Law, 2015)
This dissertation examines the plight of children in street situations in Tanzania. It also examines the obligations the State owes to children in street situations, what it has done to fulfil those obligations. It analyses the effectiveness and impact of the steps and actions undertaken to fulfil the obligations towards children in street situations.